Factors Contributing to the Accuracy of PET Scans in Detecting Cancer Metastases in Cairo Hospitals, Egypt - Sayeed, Fatmah (Phlox Institute: Indonesian Medical Research Organization, 2024)
Introduction: Positron emission tomography (PET) has become an important diagnostic tool in oncology, providing metabolic information that can aid in the detection and evaluation of cancer. However, the accuracy of PET scans in detecting cancer metastases can be influenced by various factors, including the type of cancer, location of metastases, and image acquisition protocol. This study aims to evaluate the factors that influence the accuracy of PET scans in detecting cancer metastases in patients at Cairo Hospital, Egypt. Methods: Patient data were collected retrospectively. A total of 5000 research subjects participated in this study. Data were analyzed to identify factors associated with false-positive or false-negative PET scan results. Results: Patients with lung or colorectal cancer were 2.45 times more likely to experience accurate positive PET scan results than patients with other types of cancer. Patients with metastases in lymph nodes were 1.93 times more likely to experience accurate positive PET scan results than patients with metastases in solid organs. Patients with a long PET scan image acquisition protocol were 1.78 times more likely to experience accurate positive PET scan results than patients with a short image acquisition protocol. Conclusion: PET scan is a valuable diagnostic tool in oncology, but its accuracy in detecting cancer metastases can be influenced by various factors. These factors should be considered when interpreting PET scan results and to improve cancer diagnosis and management.